Data mining a tutorial-based primer - Roiger, Richard (Addison Wesley, 2003)
This primer on data mining provides an introduction to the principles and techniques for extracting information from a business-minded perspective. A basic familiarity with the field of data mining concepts is built and then enhanced via 13 data mining tutorials.